The development and evaluation of a multimedia resource centre to support ICT training in information age: a case study of Abadina Media Resource Centre (2012)
Addressed are the issues surrounding the process of training the staff of a multimedia center in the use of Information and Communication Technology (ICT), and application of outcomes of training in the workplace. It was discussed in the context of development and evaluation of a multimedia centre with respect to supporting proper adoption and implementation of Information and Communication Technology (ICT) in information age. It highlights important issues that must be kept in proper perspective if the objectives of Information and Communications Technology (ICT) adoption to enhance perfomance on the part of staff are to be achieved. It reports on the pilot study, focusing on design issues, training needs, processes and users' experiences.